Is low iron status a risk factor for neural tube defects?. Issue 2 (18th February 2014) - Molloy, Anne M.; Einri, Caitriona Nic; Jain, Divyanshu; Laird, Eamon; Fan, Ruzong; Wang, Yifan; Scott, John M.; Shane, Barry; Brody, Lawrence C.; Kirke, Peadar N.; Mills, James L.
<x xml:space="preserve">Abstract</x> Background Folic acid supplements can protect against neural tube defects (NTDs). Low folate and low vitamin B12 status may be maternal risk factors for having an NTD affected pregnancy. However, not all NTDs are preventable by having an adequate folate/ B12 status and other potentially modifiable factors may be involved. Folate and vitamin B12 status have important links to iron metabolism. Animal studies support an association between poor iron status and NTDs, but human data are scarce. We examined the relevance of low iron status in a nested NTD case–control study of women within a pregnant population‐based cohort. Methods Pregnant women were recruited between 1986 and 1990, when vitamin or iron supplementation in early pregnancy was rare. Blood samples, taken at an average of 14 weeks gestation, were used to measure ferritin and hemoglobin in 64 women during an NTD affected pregnancy and 207 women with unaffected pregnancies. Results No significant differences in maternal ferritin or hemoglobin concentrations were observed between NTD affected and nonaffected pregnancies (case median ferritin 16.9 µg/L and hemoglobin 12.4 g/dl versus 15.4 µg/L and 12.3g/dl in controls). As reported previously, red cell folate and vitamin B12 concentrations were significantly lower in cases. Furthermore, there was no significant association of iron status with type of NTD lesion (anencephaly or spina bifida). Conclusion We conclude that low maternal iron status during early pregnancy is not an independent risk factor for NTDs. Adding iron to folic acid for periconceptional use may improve iron status but is not likely to prevent NTDs. Birth Defects Research (Part A) 100:100–106, 2014. © 2014 Wiley Periodicals, Inc.